Spatiotemporal patterns of dengue incidence and transmission dynamics in Yemen, 2020–2024 - Alhothily, Ibrahim Ahmed Ahmed; Al-Shaibah, Magdah Abdulwali Mohammed; Dapari, Rahmat; Dom, Nazri Che; Annie Tan, Geok Yuan; Teh, Chee Keng (Elsevier B.V., 2026)
AbstractProblem consideredDengue fever remains a recurrent epidemic in Yemen, yet its seasonal dynamics and regional heterogeneity are poorly characterized. Limited evidence on subnational patterns hampers timely interventions in a country already burdened by conflict and fragile health systems. This study analyzed dengue transmission from 2020 to 2024 across ten surveillance-covered governorates in Yemen, focusing on incidence trends, seasonal windows, and the effective reproduction number (Reff) to inform control strategies.MethodsWe conducted a retrospective ecological study using monthly surveillance data on probable and confirmed dengue cases from ten governorates. Population denominators were derived from Central Statistical Organization and OCHA datasets. Incidence per 100,000 population was calculated for each governorate. Harmonic regression was applied to assess seasonality, while a Cori-type method estimated Reff from disaggregated case data, assuming a gamma-distributed generation interval (mean 7 days, SD 3.5). Sensitivity analyses tested alternative intervals (5 and 9 days).ResultsA total of 105,403 dengue cases were reported. National incidence consistently peaked between May and November. Southern and coastal governorates, including Aden, Hadramawt, and Shabwah, experienced earlier and higher peaks, exceeding 150 per 100,000, while northern and inland regions exhibited later, lower peaks. Median Reff values exceeded 1 during June–November in coastal areas, confirming sustained transmission, whereas highland regions displayed shorter seasonal windows. Scenario analyses applying multipliers ranging from × 2 to × 10 scaled total burden upward across all governorates but did not materially alter the relative seasonal timing or spatial ranking of high-burden regions. These scenarios are intended to reflect plausible under-ascertainment ranges rather than calibrated burden estimates.ConclusionDengue transmission across the ten study governorates shows consistent seasonal windows with marked subnational heterogeneity. Reff-informed seasonal calendars provide a structured framework for understanding transmission phases and may support phased intervention planning when interpreted alongside surveillance trends and contextual constraints.